A COMPREHENSSIVE REVIEW ON MANAGEMENT OF HEMORRHOIDS (GUDARSHA) - AN INTEGRATED APPROACH - Amarprakash, Dwivedi; Anaya, Pathrikar; Kumar, Amitabh; Mukesh, Shukla (International Journal of Research -GRANTHAALAYAH, 2019)
Background-Haemorrhoid is a condition characterized by the prolapsed of an anal cushion that may result in bleeding and pain from rectum or anal canal. It is said to be the fourth leading outpatient gastrointestinal diagnosis. Modern medical science has treatment alternatives such as diet- lifestyle modification, sclerotherapy, banding, LASER ablation etc. in early stage and various surgical procedures such as Haemorrhoidectomy, MIPH etc. in advanced stage with varied prognosis. Haemorrhoid can be co-related with Gud-Arsha in Ayurveda. Ayurvedic texts suggest fourfold treatment for Arsha such as Bheshaj (Medicinal treatment), Kshar karma (Herbal caustic paste), Agnikarma (thermal heat burn) and Shastra karma (Surgery). Method- In this review article, information from modern surgery texts in view of definition, aetiology, patho-physiology, sign and symptoms and available treatment options as per stage of disease and a gist of contemporary texts of Ayurveda related to Arsha (Haemorrhoid) have been documented to understand integrated and holistic treatment approach towards haemorrhoid management. Result & Conclusion- The article attempts to simplify haemorrhoid management and touches maximum aspects of this disease with an integrated approach. Hence, this article will certainly prove useful to proctologist and researchers belonging to field of Modern and Ayurveda, to know about holistic haemorrhoid management.